085 Primary or secondary injury prevention in recreational runners: does it differ?. (3rd March 2020) - Fokkema, Tryntsje; Vos, Robert-Jan de; Bierma-Zeinstra, Sita MA; Middelkoop, Marienke van
Abstract : Background: A previous injury is the most important risk factor for a running-related injury (RRI). This raises the question whether RRI prevention should aim at primary or secondary prevention of RRIs. Objective: To compare the effectiveness of an injury prevention program in runners who had an RRI at baseline and runners without an RRI at baseline and in the past. Design: Randomized-controlled trial Setting: This study includes subgroup analyses of a randomized-controlled trial on RRI prevention in recreational runners registering for a Dutch running event (5–42.2 km). Participants: 540 recreational who suffered an RRI at baseline and 1140 recreational runners who did not have an RRI at baseline and in the year before the trial. Interventions: Participants that were randomized into the intervention group were given access to an online injury prevention program that consisted of information on evidence-based risk factors and advices to reduce the injury risk. Main outcome measurements: The number of new RRIs in the intervention and control group, respectively, during follow-up assessed with three follow-up questionnaires (one week before, one week after and one month after the running event). Results: Runners with an injury at baseline more often used the prevention program in their training sessions than runners without previous injuries (46.3% vs. 39.5%, p=0.02). In runners with an injury at baseline, 44.5% new RRIs occurred in the intervention group compared to 42.9% in the control group (OR 0.97, 95%CI 0.66;1.44). In the runners without a previous RRI there was a trend towards more RRIs in the intervention group (30.9% vs. 27.7%, OR 1.30, 95%CI 0.99;1.70). Conclusions: This study seems to suggest that runners without any injuries in the past may need a different approach in injury prevention. As a previous injury is the most important risk factor for RRIs, future RRI prevention measures may aim at secondary prevention of RRIs.